The Role of Islamic Religious Education Teachers in Enhancing Digital Literacy - Riyan Jaelani Salat; Veggy Xandrinata Unggari; Yogi Saepul Anwar; Gina Fauziyah; Siti Maryam Munjiat (Journal of Practice Learning and Educational Development, 2026)
This examine pursuits to investigate the role of Islamic education (PAI) instructors in improving students’ virtual literacy inside the virtual era. The research is grounded within the gap between the growing call for for digital literacy abilities and the varied capacity of teachers to integrate era into the learning process. A qualitative descriptive approach changed into hired, utilising in-depth interviews, participant observation, and documentation related to teachers engaged in technology-based instruction. The findings suggest that although instructors show robust attention of the significance of digital literacy, its implementation continues to be hindered via constrained digital competence and insufficient faculty centers. teachers with better ranges of virtual talent are capable of use era greater effectively to foster college students’ critical thinking and unbiased mastering. furthermore, collaboration amongst instructors, dad and mom, and colleges plays a tremendous role in creating a secure and effective virtual getting to know surroundings. This look at highlights the want to bolster the educational virtual atmosphere thru non-stop education, improved technological infrastructure, and multisectoral collaboration.